Paracrine signalling in colorectal liver metastases involving tumor cell-derived PDGF-C and hepatic stellate cell-derived PAK-2 - Bandapalli, Obul Reddy; Macher-Göppinger, Stephan; Schirmacher, Peter; Brand, Karsten (Clinical & experimental metastasis, 2012)
In a nude mouse model of colorectal liver metastases, we have identified a paracrine tumor cell/host cell signalling pathway that is apparently required for successful tumor growth. Whereas recombinant platelet derived growth factor-C (PDGF-C) and supernatants from PDGF-C secreting wild type LS174T colon carcinoma cells could rescue tumor promoting hepatic stellate cells (HSC) from growth inhibition by serum starvation, supernatants from LS174T colon carcinoma cells with reduced secretion of PDGF-C had much less effect on serum starved HSC. Autocrine growth inhibition of LS174T cells by PDGF-C knock-down was only marginal. In vivo, a prominent inhibition of liver metastasis was observed if PDGF-C was knocked-down in LS174T cells. By whole genome array analysis of host cells of the invasion front and subsequent immunohistochemical staining we identified p21 activated kinase-2 (PAK-2) as being strongly and specifically expressed by HSC. The above described effect of PDGF-C on HSC was found to be dependent on PAK-2 because in contrast to wild type HSC, silencing of PAK-2 in HSC only allowed for a partial PDGF-C-mediated rescue from serum starvation leading to only a slight increase of proliferation. These data indicate that PDGF-C promotes tumor growth via a growth promoting effect on HSC that is at least in part dependent on the presence of functional PAK-2.